Evaluation of protective response to hepatitis B vaccine in children at Tishreen university hospital - زريق, يوسف; وسوف, ريم (Latakia University Journal -Medical Sciences Series, 2022)
Objective: This study was undertaken to evaluate the protective response to hepatitis B vaccine in children at Tishreen university hospital, and to evaluate the study between possible the infant-feeding type and the response to the vaccine. Patients and methods: A total of 170 children aged 1-12 years including 73 girls and 97 boys gathered from pediatric department in Tishreen University Hospital. All the children in this study have undergone hepatitis B vaccine program according to the national standards (3 doses at 0, 3, 7 months after birth). Plasma anti-HBs titers were measured using ELISA method. Samples that were positive for Anti-HBs were then tested for the presence of Hbc-Ab in order to differentiate between immunity resulting from vaccination and that resulting from past infection Results: Children who had a titer higher than 100 mIu/mL were considered as protective responders. Our results revealed that this rate was (47.6%). On the other hand, there was no significant differences between girls and boys regarding the immune response (P = 1) which means there was no significant association between level of response and gender. In addition, the statistical analyses showed that there was no relation between the infant feeding type and the protective response rate (P = 0.8). Conclusion: The protective response rate to HBV vaccine in our study was 47.6%. There was no relation between gender or type of infant feeding with the protective response to HBV vaccine.